Analisis Implementasi Standar Proses pada Pembelajaran Akuntansi SMK Negeri di Kota Padang - Dede Firman (Universitas Negeri Padang, 2022)
The purpose of this study is to analyze the implementation of the standard process in the accounting learning, State Vocational Schools in Padang City. This type of research is descriptive. The population in this study are teachers in accounting departmen at State Vocational Schools in Padang City, amounting to 24 people. The research instrument is questionnaire. The data analysis technique uses the descriptive analysis. The results of data analysis show that the implementation of Process Standards in Accounting Learning at State Vocational Schools in Padang City is in terms of: 1. the requirements for implementing the process are in the good category (3.61), 2. preliminary activities are in the good category (3.54), 3. core activities in good category (3, 65), 4. closing activity in good category (3,61), 5. Attitude Core Competence Assessment in good category (3,78), 6. Knowledge Competency Assessment in good category (3,80), 7. Skills Competency Assessment in good category (3,81). The results of this study can be used as a guide in improving the quality of the accounting learning especially in Accounting Department.